Screening global set of barley germplasm for resistance to spot blotch disease in the warm-humid plains of Nepal - Pokharel, Bhanu Bhakta; Pandey, Madhav Prasad; Ghimire, Surya Kant; Thapa, Dhruba Bahadur; Manandhar, Hira Kaji; Rijal, Tirtha Raj; Thapa, Sailendra; Adhikari, Parbati; Verma, Ramesh Pal Singh; Gyawali, Sanjay (Journal of Cereal Research, 2021)
Spot blotch disease (SB) caused by Bipolaris sorokiniana (teleomorph: Cochliobolus sativus) is a major disease of barley and causes a significant yield loss under favorable conditions in the warm and humid areas. A global set of 340 barley germplasm obtained from ICARDA were evaluated for SB resistance under natural epiphytotic conditions along with two local checks (Bonus and Solu Uwa) at the research field of Nepal Agricultural Research Council, Rampur, Chitawan, Nepal for three consecutive years (2016-2018). Analysis of variance showed significant variation in Area Under Disease Progress Curve (AUDPC) of the studied genotypes in all the three yearsâ€™ experiments. The check varieties were susceptible to SB (AUDPC value â‰¥ 750) in all the experiments. In the first-year experiment, 28, 105, 98 and 109 genotypes had resistant (R, AUDPC